Early Thoracic Endovascular Aortic Repair of Uncomplicated Type B Thoracic Aortic Dissection: An Aorta Team Approach - Ammar, Khawaja A.; McDiarmid, Matthew; Richards, Lauren; Mewissen, Mark W.; Jan, M. Fuad; Weiss, Eric S.; Bajwa, Tanvir (AORTA, 2023)
Background Although uncomplicated Type B aortic dissection (uTBAD) is traditionally treated with optimal medical therapy (OMT) as per guidelines, recent studies, performed primarily in interventional radiology or surgical operating rooms, suggest superiority of thoracic endovascular aortic repair (TEVAR) over OMT due to recent advancements in endovascular technologies. We report a large, single-center, case control study of TEVAR versus OMT in this population, undertaken solely in a cardiac catheterization laboratory (CCL) with a cardiologist and surgeon. We aimed to determine if TEVAR for uTBAD results in better outcomes compared with OMT.Methods This was a retrospective chart review of all patients with uTBAD during the last 13 years, with 46 cases (TEVAR group) and 56 controls (OMT group).Results In the TEVAR group, the procedure duration of 2.5 hours resulted in 100% procedural success for stent placement, with 63% undergoing protective left subclavian artery bypass, 0% mortality or stroke, and a lower readmission rate (1 vs. 2%; p = 0.04 in early TEVAR cases), but a longer length of stay (12.9 vs. 8.5 days: p = 0.006). The risk of all-cause long-term mortality was markedly reduced in the TEVAR group (RR = 0.38; p = 0.01), irrespective of early (<14 days) versus late intervention. On follow-up computed tomography imaging, the false lumen stabilized or decreased in 85% of cases, irrespective of intervention timing.Conclusion TEVAR performed solely in the CCL is safe and effective, with lower all-cause mortality than OMT. These data, in collaboration with previous data on TEVAR in different settings, call for consideration of an update of practice guidelines.
Keywords: aneurysm; aortic dissection; endovascular repair; thoracic aorta